Unidade de ensino potencialmente significativa com enfoque CTS para abordar o tema da extração mineral - Trento, Elisandra (2019)
The present study is based on the need to implement and evaluate didactic proposals that arouse interest and facilitate the learning of chemical concepts in high school students . The objective of the proposal was to analyze the pertinence of working the contents of solutions and oxidation organized in the form of a Potentially Significant Teaching Unit ( PSTUs) with a Science-Technology-Society (STS) approach based on the mineral extraction in Brazil. The main theoretical contribution used in the present study was the Theory of Significant Learning of David Ausubel, complemented by the contributions of Marco Antonio Moreira through the PSTUs. The problem that led to the development of the study is based on the understanding that Chemistry teaching is generally decontextualized and confined to traditional forms of teaching, offering few alternatives for the meaningful appropriation of chemical concepts. The work was guided by the questions: to what extent does the PSTUs show a methodology that allows the approach of the themes with a STS approach? How do students react to didactic interventions involving problem situations? Is it possible to integrate the contents of solutions and oxidation through a PSTUs? The research carried out is characterized by a qual itative, participant nature, structuring its data collection in two instruments: the researcher's logbook and the materials made by the students. This study was carried out in a public school of the state education network in the municipality of Marau, RS with twelve students of the second year of polytechnic high school in the afternoon shift. The results of the study, revealed by the collection instruments, through the application of several didactic strategies such as: problem situations, experimental activities, the extractive company indicate the potentiality of the proposal, mainly for awakening students' participation, curiosity and interest . The present dissertation is accompanied by an educational product, intended for high school teachers, which is a structured booklet in the form of a PSTUs, entitled “Study of Solutions and Oxidation through Mineral Extraction”. This product is available at <http://educapes.capes.gov.br/handle/capes/432291>.